2020
DOI: 10.3390/ijerph17238954
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Aerosol Contamination in Dental Procedures during the Second Wave of COVID-19—Experience and Proposals of Innovative IPC in Dental Practice

Abstract: Dental-care workers operate very close to the patient’s mouth and are at high risk of contamination by SARS-CoV-2. Droplets may be contaminated by patient’s saliva and exhaled breath particles. All asymptomatic patients should be considered as Coronavirus positive. All dental procedures must be revised after positive identification of SARS-Cov-2. Novel recommendations as the use of novel suction cannula designed for fast spray/saliva aspiration, use of Tyvek suits and innovative sprayhoods designed for dental-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
(56 reference statements)
1
26
0
1
Order By: Relevance
“…Interestingly, in this paper, the WMSD prevalence is high in dental specialists (41.9%) and general practitioners (29.2%) and lower for dental hygienists (24.2%). Dentists specialists, general practitioners use highspeed and micromotor handpieces very frequently for removal of caries, root canal treatments, restorations and various other procedures [ 3 ]. Moreover, recurrent movements of the hand and fingers during use of hand files and broaches for root canal procedures lead to a repetitive stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in this paper, the WMSD prevalence is high in dental specialists (41.9%) and general practitioners (29.2%) and lower for dental hygienists (24.2%). Dentists specialists, general practitioners use highspeed and micromotor handpieces very frequently for removal of caries, root canal treatments, restorations and various other procedures [ 3 ]. Moreover, recurrent movements of the hand and fingers during use of hand files and broaches for root canal procedures lead to a repetitive stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with the onset of the Sars-Cov2 pandemic, the use of additional protective devices increases the mental stress, the risks of imbalanced postures and further reduces the freedom of movements [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…• Continuous vigilance to early detect and properly manage a COVID-19 case in the school • Implementation of dental AGPs with the appropriate procedures to reduce the production of aerosol • Strict compliance with infection prevention and control measures focusing on hand hygiene, appropriate use of PPE and cleaning/disinfection • Training of students and personnel in infection control practices • The Heating Ventilation and Air Conditioning (HVAC) system should fulfill at least the minimum requirements for SARS -CoV-2 in dental settings. It should be noted that new operative and clinical dental procedures and risk-scoring systems of safety protocols are being currently developed by university dental clinics and hospitals in an attempt to reduce risk for dentists, dental personnel and patients [33,34]. Similarly, there is an increasing number of publications about the benefit of specific interventions on aerosol contamination, however further studies are needed on focusing on respiratory agents such as SARS-CoV-2 [35].…”
Section: Principals For Preparing Dental Schools During the Covid-19mentioning
confidence: 99%
“…This finding conforms to our study in which the amount of aerosol was found mostly at a distance of 12-inches after 30 min and almost no aerosol at farther distances, although a significant reduction was noticed after 30 min compared to the time of immediate cavity preparation. Therefore, to reduce the risk of contamination from airborne pathogens, especially in this era of the COVID-19 pandemic, it is recommended that practitioners keep wearing their personal protective barriers after the completion of the procedure for a certain period [ 27 ].…”
Section: Discussionmentioning
confidence: 99%